Rapid identification of α-glucosidase inhibitors from Poria using spectrum-effect, component knock-out, and molecular docking technique - Ma, Changyang; Lu, Jie; Ren, Mengjie; Wang, Qiuyi; Li, Changqin; Xi, Xuefeng; Liu, Zhenhua (Frontiers in Nutrition, 2023)
Poria (Poria cocos) is used as a food with health promoting effects, including hypoglycemic activity. However, the composition of Poria is complex and the bioactive compounds that inhibit α-glucosidase are not clear. In this study, the fingerprint of the Poria methanol extract characterized by high performance liquid chromatography (HPLC) and the model of corresponding spectrum-effect relationship for α-glucosidase were first established to screen the active compounds from Poria. Then the predicted bioactive compounds were knocked out and identified by mass spectrometry. Finally, the potential binding sites and main bonds of each compound with α-glucosidase were studied by molecular docking. Results have showed that at least 11 compounds from Poria could inhibit α-glucosidase effectively. Moreover, 8 individual compounds, i.e., poricoic acid B (P8), dehydrotumulosic acid (P9), poricoic acid A (P10), polyporenic acid C (P12), 3- epidehydrotumulosic acid (P13), dehydropachymic acid (P14), 3-O-acetyl-16α-hydroxytrametenolic acid (P21) and pachymic acid (P22) were identified and they exhibited effective inhibitory activity against α-glucosidase. The molecular docking showed that the binding sites are mainly in the rings A, B and C of these compounds, and C-3 C-16 and side chains of C-17, with the phenylalanine, arginine, tyrosine, histidine, valine of α-glucosidase. The main interactions among them might be alkyl and hydrogen bonds, which theoretically verified the inhibitory activity of these compounds on α-glucosidase. The achievements of this study provided useful references for discovering bioactive compounds with hypoglycemic effect from Poria.